Evaluating in Situ Water and Soil Conservation Practices with a Fully Coupled, Surface/Subsurface Process‐Based Hydrological Model in Tigray, Ethiopia - Opolot, Emmanuel; Araya, Tesfay; Nyssen, Jan; Al-Barri, Bashar; Verbist, Koen; Cornelis, Wim M. (Land Degradation & Development, 2016)
In situ water and soil conservation (WSC) practices are a promising intervention to improve rainwater management particularly in the semiarid to dry sub-humid tropics. This study applies a fully coupled surface–subsurface process-based model (HydroGeoSphere) to simulate in detail rainwater partitioning as affected by two in situ WSC practices [terwah+ (TER+) and derdero+ (DER+)] currently under study on Vertisols in Tigray, Ethiopia and to evaluate the treatments in terms of rainwater partitioning. In the TER+ practice, contour furrows of 0·2m wide and 0·1m deep are created at 1·5m intervals between permanent broad beds, whereas in DER+, permanent raised beds 0·6m wide with furrows 0·2m wide and 0·1m deep are created, to minimize runoff and water logging. The model accurately reproduced measured surface runoff (e.g. in DER+: Nash–Sutcliffe model efficiency E = 0·6 for calibration and 0·7 for verification) and soil moisture content (DER+: E = 0·6 for calibration and 0·8 for verification). Runoff depth was lowest under DER+ (50 mm) followed by TER+ (67 mm) and significantly higher in conventional tillage (CT) (160 mm). Simulated transpiration, evaporation and drainage out of the root zone were all higher under DER+ and TER+ compared with CT. The effects of DER+ and TER+ practices on rainwater partitioning were more pronounced in wet years than in dry years. The model proved to be a promising and versatile tool to assess the impact of WSC practices on rainwater partitioning at the field scale.
Keywords: Surface-subsurface flow model; Water and soil conservation